2005
DOI: 10.1037/0022-0167.52.4.490
|View full text |Cite
|
Sign up to set email alerts
|

White Racial Identity Dyadic Interactions in Supervision: Implications for Supervisees' Multicultural Counseling Competence.

Abstract: Examining supervisory dyads consisting of a White supervisor and a White supervisee, the authors sought to determine the effects of similarities and differences in levels of supervisor and supervisee racial identity schemas or attitudes on White supervisees' self-reported multicultural counseling competence and multicultural case conceptualization ability. White supervisees in supervision dyads characterized by more advanced White racial identity schemas reported higher self-perceived multicultural counseling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
(65 reference statements)
1
30
0
Order By: Relevance
“…Ethnic identity has been found to positively correlate with higher levels of MCC (Constantine, Warren, & Miville, 2005;Neville et al, 1996;Ottavi, Pope-Davis, & Dings, 1994;Vinson & Neimeyer, 2003). For example, Ottavi et al (1994) found that White counselors who had more advanced racial identity development (defined as having reached the Pseudo-Independence stage of racial identity) had a stronger predictive relationship to self-reported MCC.…”
Section: Ethnic Identity and MCCmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic identity has been found to positively correlate with higher levels of MCC (Constantine, Warren, & Miville, 2005;Neville et al, 1996;Ottavi, Pope-Davis, & Dings, 1994;Vinson & Neimeyer, 2003). For example, Ottavi et al (1994) found that White counselors who had more advanced racial identity development (defined as having reached the Pseudo-Independence stage of racial identity) had a stronger predictive relationship to self-reported MCC.…”
Section: Ethnic Identity and MCCmentioning
confidence: 99%
“…More than a decade after Ottavi et al's study, Middleton et al (2005), in a near replication of Ottavi et al's study, reported that the racial identity status of mental health practitioners was again positively related to their perceived MCC. Previous studies of ethnic identity and MCC tend to take one of three typical analytic approaches: (a) ethnic identity is one of the predictor variables in a regression analysis in which MCC measurements are criterion variables (Ottavi et al, 1994), (b) ethnic identity is an independent variable (using racial identity categories rather than ethnic identity as a continuous measure) and MCC measurements are dependent variables in a MANOVA (Constantine et al, 2005), or (c) no mediator is included between ethnic identity and MCC (Chao, 2008). Middleton et al (2005) urged researchers to conduct more advanced structural equation analyses rather than correlation or regression analyses to further determine the relationship that exists between ethnic identity and MCC.…”
Section: Ethnic Identity and MCCmentioning
confidence: 99%
“…Because oppression based on external features occurs ubiquitously, Black and Brown supervisors may be more aligned with the subordinate status associated with their race rather than the power afforded to their supervisory role. As a result, supervisors of color may be more informed regarding the privilege of White supervisees and clients, while White supervisees may be unfamiliar with the subordination and disempowerment of racialized supervisees and clients (Burkard, et al, 2014;Constantine, Warren, & Miville, 2005). Lived experiences of power and privilege, or the lack thereof, are likely to manifest in complementary approaches to supportive supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some authors focused on developing models for multicultural supervision, others explored the relationship between supervisor and supervisee, specifically focusing on diverse identities each person brings to the relationship. It has been asserted that the demographic variables of the supervisor and supervisee (e.g., gender, race/ethnicity, sexual orientation, age, spiritual/religious beliefs, and physical ability) affect the supervisory relationship (Constantine, 2003;Constantine, Warren, & Miville, 2005;Cook, 1994;D'Andrea & Daniels, 1997;Granello, 2002;Helms, 1984;Ladany, Brittan-Powell, & Pannu, 1997). The intersection of identities within each person and the individual's respective identification with each of the demographic groups can result in complex interactions between supervisor and supervisee.…”
Section: Supervisory Relationship and Multiculturalismmentioning
confidence: 99%